Consequential Intersections: Examining Equity Expressions and Experiences Within Special Education Ecosystems - Catherine Kramarczuk Voulgarides; Sarah L. Woulfin; Natasha Strassfeld; Isabel Meltzer (SAGE Publishing, 2024)
We employ the metaphor of an educational ecosystem to explain how racial inequity in special education manifests in a midsized urban school district via equity expressions and experiences. We focus on two ecosystems operating at the mesol-evel within school districts:1) special education and 2) equity ecosystems. We show how these educational ecosystems converge and diverge when a state education agency (SEA) cites a local education agency (LEA) via federal disability legislation for racial disparities in special education outcomes-commonly referred to as racial disproportionality. Using document analysis and semistructured interview data, we empirically examine how equity and special education ecosystems converge and diverge and discuss the implications for addressing racialized inequities. We highlight that there was limited equity absorption across the two ecosystems and how racism and ableism are implicated in the convergences and divergences between the two systems. We conclude with recommendations for policy and practice.